Search 72,410 tutors
FIND TUTORS
Ask a question
1 0

-2(x-14)=26

Tutors, please sign in to answer this question.

3 Answers

Hello!

 

It's important to know why you need to follow the steps you need to solve this problem, so you can solve other ones like it in the future. :)

We have to make x stand alone to find out this answer, so to do that, we need to first get rid of the -2 and the -14.  The way to do that is to do the opposite of what they are doing in the problem now.  Right now, the problem is -2 TIMES (x MINUS 14) on one side, so to get rid of the -2, we need to DIVIDE both sides by -2, then ADD 14 to both sides. 

Step 1: Divide both sides by -2

-2(x-14) divided by -2 is (x-14)

and 26 divided by -2 is -13

so, that leaves us with x-14 = -13

 

Step 2: We need to get rid of the -14 (so that x will be by itself on one side)

So, we do the opposite of what is happening in the problem again. Which means that we ADD 14 to both sides.

x-14 Plus 14 leaves us with just x

-13 Plus 14 leaves us with 1

So, we are left with x=1

And that is the answer! :)

 

We will use distributive property of multiplication:
a(b ± c) = ab ± ac
~~~~~~~~~

   -2( x – 14) = 26

   -2x – (-2) * 14 = 26

   -2x + 28  =  26
         - 28    - 28

   -2x   =   -2
÷(-2)     ÷(-2)

     x = 1 
Verify the answer:
 -2(1 - 14) = 26
  -2(-13) = 26
      26 = 26

Woodbridge tutors